التشوهات المعرفية و علاقتها بدافعية التعلم لدى طلبة جامعة الأغواط - بداوي خديجة; صفية مشكل; أحمد بن سعد (My University, 2021)
Our study aimed to reveal the existence of a correlation between cognitive distortions and learning motivation among a sample of university students, and our study followed the descriptive approach using one-sample t-test and Pearson correlation coefficient, the data was processed using a statistical package for social sciences spss. The study was applied to a sample of students (64 students) from 03 faculties at Ammar Thilji University in the state of Laghouat for the academic year 2020/2021, through a questionnaire distributed to them, where the results resulted in the following outcome: - There is a correlation between cognitive distortions and the level of motivation to learn - The level of cognitive distortions is low among the study sample members - The level of motivation to learn is high among the study sample members cognitive distortions; learning motivation; Undergraduate student